Phosphoregulation of divergent cell division in Protozoan parasites - Brusini, Lorenzo (2019)
Cell cycle machinery comprises a network of regulatory switches and checkpoints that control the progression of nuclear replication, chromosome segregation and cell division in all complex cells. Decades of research – predominantly in animal or fungal models – has uncovered critical components of this network, in particular demonstrating the essential roles played by specific kinases and phosphatases. Several key players in the network are conserved between humans and yeast, leading to a common assumption that the machinery is similar across all eukaryotes. However, animals and fungi represent only a small subsection of the diversity of eukaryotic cell division. Protozoan parasites represent excellent models to study eukaryotic cell division because: i) they are members of eukaryotic groups that diverged from animals/fungi at or near the origin of eukaryotes, ii) they often divide in ways that are different from canonical models, and iii) due to their importance for human health, they represent some of the best studied cells outside of animal/fungal models. Here, I present work on the phosphoregulation of cell division in two significant groups of parasites – the Apicomplexa, which include the causative agent of malaria, and Kinetoplastida, which cause sleeping sickness and Leishmaniasis.